The role of the helots in 'educating' the Spartans - L.G. Pechatnova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers and analyzes the ancient sources mentioning the role played by the helots in the upbringing of sons of Spartan citizens. The focus is on the ways and forms through which the helots were exploited to educate the young generation there. The status of the helots poses a significant challenge to researchers because there are few sources on this issue, mostly dated back to a later period. Thus, all observations and reasoning can be only hypothetical at present.